(untitled) (Research, Society and Development, 2022)
The most relevant forest species in Brazil are eucalyptus (Eucalyptus grandis W. Hill ex Maide) and pine (Pinus elliottii Engelm). The present study aimed to review the legal aspects for the production, processing, storage, commercialization and transport of seeds and seedlings of forest species, to elucidate the main positive and negative points of the legislation. He mentioned Law No. 10,711, of August 5, 2003. Subsequently, he highlighted Decree No. 10,586, of December 18, 2020, which regulates Law No. 10,711, of August 5, 2003, which provides for the System National Seeds and Seedlings. For forest species, the main normative instructions to be considered are Normative Instruction No. 17, of April 26, 2017, Normative Instruction No. 19, of May 16, 2017, Normative Instruction No. 43, of December 15, 2015, Instruction Normative No. 34, of September 9, 2014 and Normative Instruction No. 44, of December 23, 2010. For the production of seedlings, Normative Instruction No. 24, of December 16, 2005 and Normative Instruction No. 42 of October 13, 2009, to regulate the production and sale of seedlings of forest species. The laws, decrees and normative instructions referring to the sector of seeds and seedlings of forest species are important tools to help in the maintenance of the quality of the final product, however it is necessary to update some normative instructions, decrees and laws, which involve the sector of seeds and seedlings of forest species, since there is a time lag.